Farmers’ Perception and Access to Mechanization in Maize Production in Kamwenge District, Western Uganda - Natumanya, Hillary; Kalibwani1, R.; Ssemakula, E. (Journal of Scientific Research & Reports, 2021)
Farm mechanization has been an important aspect in bringing out a significant improvement in agricultural productivity. In Uganda, mechanization acts as a backbone of the present agricultural systems across the country. Despite its recognized role towards agriculture, farmers still perceive its use and need differently mainly in terms of hire costs, traditional culture, size and topography of land, availability and social status. The study was examining farmers’ perceptions towards mechanization in maize production in Kanara sub-county in Kamwenge district. The objectives were to: determine farmers’ perceptions on the usefulness of mechanization on maize production, determine the relationship between socio-economic characteristics and farmers’ perception of mechanization, identify the factors limiting the use of agricultural mechanization among maize farmers, and to establish how best agricultural mechanization could be promoted for sustainable production. The study employed a cross-sectional survey design engaging both qualitative and quantitative approaches for data collection and analysis. Information was gathered from 362 respondents using questionnaire and interviews. Data was analyzed using SPSS version 20 to generate both descriptive and inferential statistics. Farmers’ perceived mechanization to perform more work than humans, reliable, time saving, and accessible and high work accomplishment rate. Farmerperceptions were influenced by socio-economic characteristics for example; age, land size, gender, income level/status, employment status, type of land owned and availability of labor. The study identified the challenges associated with the use of agricultural mechanization such as; less access to mechanization information significant at 5%, land ownership type at 0.03 (5%), household size 0.03 (5%), access to credit 0.04 (5%), years in maize farming at 0.05 (5%), availability and access to implements at 0.09, high costs of hire at 0.02 (1%), slope of the land at 0.07, and fuel costs at 0.00 (1%). These would be solved by extending credit services to the farmers, community capacity building, awareness creation, group formation, promoting mechanization as part of production, establishing contract farming schemes, increasing investment in agricultural mechanization, training and education and forming public–private partnerships. The study concluded that farmers had varying perceptions about agricultural mechanization which depended mainly on socio-economic factors. It recommended the need to promote rural-urban migration as this could create more land and encourage farmers to adopt mechanization since it may create more land reserve.
Keywords: Farmers’ perceptions; Maize production; Mechanization